Carbonic anhydrase 12 gene silencing reverses the sensitivity of paclitaxel in drug-resistant breast cancer cells - Ting Huang (Taylor & Francis Group, 2021)
This study aimed to investigate the effects of carbonic anhydrase 12 (CA12)-siRNA on the paclitaxel sensitivity of breast cancer cells. Normal mammary glandular cell (MCF-10), breast cancer cell (MCF-7), and paclitaxel-resistant breast cancer cells (MCF-7 TaxR) were cultured in experimental control group. Western blot was adopted to detect the expressions of CA12 protein and apoptosis-related proteins in mitochondrial pathway of MCF-10, MCF-7, and MCF-7 TaxR cells. The methylthialazole tetrazolium (MTT) method was used to measure cell proliferation. The apoptosis of MCF-7 and MCF-7 TaxR cells was observed in phase contrast microscope, fluorescence inverted phase contrastmicroscope, and flow cytometry (FACS). The results showed that CA12 protein expression in MCF-7 and MCF-7 TaxR cells was significant higher than that in MCF-10 cell. The growth rate of CA12-siRNA treated MCF-7 TaxR cells with paclitaxel (PTX) co-culture was markedly declined at 48 hours. Phase contrast microscope, fluorescence inverted phase contrastmicroscope, and FACS showed that apoptotic cells in the CA12-siRNA treated MCF-7 TaxR groups were significantly higher than that in CA12-siRNA treated MCF-7 cells. The expressions of pro-apoptotic proteins, Bax and Bid, were dramatically increased in CA12 siRNA treated MCF-7 TaxR cells. The expression quantity of the downstream effective molecules caspase-9, caspase-7, and the activated proteins of poly (ADP-ribose) polymerase (PARP), also were significantly increased. Our results indicated that the application of PTX combined silencing CA12 was able to activate the mitochondrial apoptosis pathway and promote MCF-7 TaxR apoptosis. CA12 silencing in the PTX-resistant breast cancer cell can reverse the sensitivity of PTX.